Fiscal decentralisation in the EU and its iteraction with EU's fiscal rules - Provazníková, Romana (Univerzita Pardubice, 2003)
The article considers the issue how fiscal federalism affects the capacity of Member State to achieve sound and sustainable finances as the Treaty and SGP obligations concern the general government as a whole, i.e. central state and local government plus social security. Article provides a brief over view of the allocation of resposibility for public expenditure and revenues items across level of government, and examines how this interacts with the EU framework for fiscal surveillance. Consideration is given to various institutional arrangements that have been put in place by Member States to co-ordinate the budgetary positions across levels of government, in part to comply with the provisions of the Treaty and SGP.
Keywords: Fiskální politika; decentralizace; Evropská Unie